1994
DOI: 10.1007/bf02250916
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in the etiology of idiopathic Parkinson's disease

Abstract: Overshadowed by a vigorous search for an environmentally-derived toxin that would be possibly relevant for the pathogenesis of idiopathic Parkinson's disease (PD), genetic factors have largely been neglected for this condition during the last two decades. Recent descriptions of kindreds over three or more generations with several family members affected have renewed the interest in genetics of PD. Concurring with this, diagnostic concepts and pathologic criteria for PD and for idiopathic Lewy-body (LB) disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 145 publications
0
12
0
1
Order By: Relevance
“…Cases were consistently more likely than controls to have an affected family member: roughly three to four times more likely in birth cohort and sex adjusted analyses and six times more likely in birth cohort, sex, and other risk factoradjusted analyses (Table II). Many studies have found family history of PD [Alonso et al, 1986;Duvoisin et al, 1969;Lazzarini et al, 1994;Marder et al, 1996;Martilla and Rinne, 1976;Martin et al, 1973;Payami et al, 1994;Seidler et al, 1996;Semchuk et al, 1993;Vieregge and Heberlein, 1995;Wang et al, 1993] and family history of tremor [De Michele et al, 1996;Jankovic et al, 1995;Morano et al, 1994;Vieregge, 1994] to be major risk factors for PD and with odds ratios of *Second-and third-degree relatives (aunts, uncles, grandparents, cousins) similar magnitude. We find a similar risk to parents and siblings for PD, which is consistent with an autosomal dominant mode of inheritance with reduced penetrance.…”
Section: Discussionmentioning
confidence: 88%
“…Cases were consistently more likely than controls to have an affected family member: roughly three to four times more likely in birth cohort and sex adjusted analyses and six times more likely in birth cohort, sex, and other risk factoradjusted analyses (Table II). Many studies have found family history of PD [Alonso et al, 1986;Duvoisin et al, 1969;Lazzarini et al, 1994;Marder et al, 1996;Martilla and Rinne, 1976;Martin et al, 1973;Payami et al, 1994;Seidler et al, 1996;Semchuk et al, 1993;Vieregge and Heberlein, 1995;Wang et al, 1993] and family history of tremor [De Michele et al, 1996;Jankovic et al, 1995;Morano et al, 1994;Vieregge, 1994] to be major risk factors for PD and with odds ratios of *Second-and third-degree relatives (aunts, uncles, grandparents, cousins) similar magnitude. We find a similar risk to parents and siblings for PD, which is consistent with an autosomal dominant mode of inheritance with reduced penetrance.…”
Section: Discussionmentioning
confidence: 88%
“…In the absence of a clearly identifiable cause for IP, it is assumed that some degree of genetic predisposition to the disease must exist (reviews: Vieregge, 1994;Golbe, 1995;Duvoisin, 1996). However, despite intensive investigation of a number of candidate genes, the specification of this involvement remains problematic.…”
Section: Genetic Factorsmentioning
confidence: 98%
“…La proportion des formes familiales de la maladie de Parkinson est difficile à estimer, mais les études basées sur l'anamnèse, qui comportent un biais systématique [72], rapportent une prévalence d'environ 10 à 15% de cas avec au moins un membre direct de la famille atteint [73]. Les formes monogéniques connues n'en constituent qu'une minorité, la plus fréquente étant PARK 2, retrouvée chez 49% des cas débutant avant 45 ans dans les familles à transmission autosomique récessive [41], responsable de 9 à 18% des parkinsonismes du sujet jeune, mais de moins de 1% de tous les cas de la maladie de Parkinson.…”
Section: Importance Des Formes Familiales De La Maladie De Parkinsonunclassified